Unstable Angina - Bleifeld, Walter; Hamm, Christian W.; Braunwald, Eugene (Springer Berlin Heidelberg, 1990)
A critical phase in coronary heart disease, unstable angina, is thoroughly discussed in contributions by well-known experts. Since myocardial infarction still belongs to the main causes of death, this topic is highly relevant for the present research and possible future treatment of coronary heart disease. The major recent advances made in the pathophysiology, diagnosis and therapy of unstable angina are reported in depth
Keywords: Cardiology; Pathology; Pharmacology/Toxicology; Nuclear Medicine; Toxicology; Nuclear medicine; Herzkrankheit; Ischämie; Instabile Angina pectoris; Konferenzschrift -- 1989 -- Hamburg; Aufsatzsammlung